2017
DOI: 10.3390/plants6040051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicon Amendment on Soilborne and Fruit Diseases of Avocado

Abstract: The effects of silicon (Si) amendment have been studied in several plant/pathogen interactions; however, studies in horticultural tree crops are limited. Effects of amendment with soluble potassium silicate (AgSil®32, approximately 30% available Si), or milled cement building board by-products (Mineral Mulch (MM) or Mineral Dust (MD), containing 5% available Si) were investigated in field and greenhouse trials with avocado. Orchard soil drench applications with potassium silicate improved yield and quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…In experiment 2 mineral mulch (T7) showed the lowest damage. Mineral mulch 1 (T7) contains silicon, which is known to improve root growth and increase defence mechanisms of roots when infected with Phytophthora (Bekker et al 2006; Bekker et al 2007; Bekker 2011; Dann and Le 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In experiment 2 mineral mulch (T7) showed the lowest damage. Mineral mulch 1 (T7) contains silicon, which is known to improve root growth and increase defence mechanisms of roots when infected with Phytophthora (Bekker et al 2006; Bekker et al 2007; Bekker 2011; Dann and Le 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Si concentration in the tested formulations varied a lot in the different experimental conditions. Under open field conditions, drenching applications generally were performed at higher Si concentrations (178-280 mM Si) [66,67] as compared to foliar sprays (0.05-98.2 mM Si) [35,68]. Under greenhouse conditions, with potted plants, Si was applied to the leaves or by fertigation at low concentrations, ranging from 0.08 to 0.5 mM Si [40,69].…”
Section: Silicon Application Methods To Increase Yield and Qualitymentioning
confidence: 99%
“…However, concerning the Si efficiency on the plant's life cycle, Epstein and Bloom (2005) recommended that the proper need of Si element is significant for normal plant growth. Recently, numerous researches have demonstrated that Si mitigates the destructive effects of biotic stresses (pests and diseases) (Dann and Le, 2017;Yang et al, 2017) and abiotic stresses (drought, heavy metal toxicity and salinity) in plants (Biju et al, 2017;Hasanuzzaman et al, 2018;Tayyab et al, 2018b). These benefits are attributed to Si application; thus, Si can play a serious role in order to mitigate drought stress in plants.…”
Section: Introductionmentioning
confidence: 99%